Serangan Sitophilus oryzae Pada Beras Dari Beberapa Varietas Padi dan Suhu Penyimpanan - Rizma Dwi Mastuti; Subagiya Subagiya; Retno Wijayanti (Agrosains : Jurnal Penelitian Agronomi, 2020)
Post-harvest with storage are important to maintain the supply of rice. One of the obstacles found in storing rice is the attack of Sitophilus oryzae which is responsible of causing yield loss. The attack of S. oryzae on rice can be caused by storage temperature and protein content on rice. The objective of this research was to determine the attack rate of S.oryzae in several paddy varieties and different storage temperatures. The research was conducted in Laboratory of Pest and Plant Disease Faculty of Agriculture Universitas Sebelas Maret from March-June 2019. The method used was Nested Design with 2 factors and 3 replications. The treatments given were storage temperature (29oC, 39oC, 49oC and 59oC) and paddy varieties (brown rice, black rice, Rojolele and IR64). Observation variable were number of imago, pupae, larvae, percentage of decrease in rice weight, broken rice and rice powder. The results showed that S. oryzae was able to survive at a storage temperature of 29oC. Storage temperatures which increased by more than 29°C causing mortality of S.oryzae up to 100%. The longer storage time will cause an increase in population and S.oryzae attack rate.